IMPLEMENTASI INFORMASI GIZI DENGAN TOKOH PEWAYANGAN UNTUK PENINGKATAN PENGETAHUAN GIZI SANTRI PONDOK PESANTREN - Elita Endah Mawarni; Dea Amanda Caressa; Mulya Agustina (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Nutritional problems among school-aged children, including students in Islamic boarding schools (pesantren), remain a significant issue due to their impact on growth, cognitive development, and quality of life. The pesantren environment, characterized by a tight schedule, limited dietary variety, and low nutritional knowledge, poses a risk of unbalanced dietary patterns and long-term health problems. This study aimed to assess the effectiveness of nutrition education using wayang (traditional puppet) media on the nutritional knowledge of students at Pondok Pesantren Safinatul Huda, Banyuwangi. The methods employed included balanced nutrition socialization, education on the six food groups, demonstration of menu preparation using local ingredients (purple sweet potato), and delivery of materials through wayang characters as an engaging and memorable cultural medium. The study sample consisted of 40 junior high school students (santri). Data were analyzed using the Paired Sample T-Test to evaluate differences in nutritional knowledge before and after the intervention. The results showed a significant increase in the mean nutritional knowledge score from 72.15 to 77.90 (p < 0.001). Wayang media proved effective in enhancing understanding, motivating the adoption of healthy eating patterns, and providing a culturally relevant and contextual educational approach.